Rapid Screening Methods for Universal Binding Peptide Aptamers Against SARS-CoV-2 Variant Spikes, Including Omicron Variants, and their Application to Diagnostic and Therapeutic Agents - Hayashi, Nakanobu; Abe, Chikako; Kikuchi, Jiro; Hayashi, Momoko; Hayashi, Sakura; Ueda, Masahiro; Suzuki, Koyu; Sugitani, Masahiko; Taniguchi, Hiroaki; Wake, Toru; Furukawa, Yusuke (Archives of Clinical and Biomedical Research, 2024)
The development of mRNA vaccines and oral drugs against SARSCoV- 2 has been useful in protecting against Covid-19 infection. Since then, however, many variants of delta and omicron strains with enhanced infectivity and immune escape capacity have emerged. A 7-amino acid random peptide ribosome display library screening system was used to perform a rapid in vitro screening of peptide aptamers that universally bind to the SARS-CoV-2 wild-type, delta, and Omicron variant BA.1, BA.2, and BA.5 spike RBD (Receptor Binding Domain). Screening resulted in four peptide aptamers that showed positive binding reactions in ELISA. Interestingly, Amino Acid Sequence Determination of the four clones predicted that three of the four clones contain 2~3 Cys residues in their sequences, forming a complex higher-order structure with disulfide (S-S) bonds. The 7-amino acid random peptide ribosome display library screening system allows for rapid in vitro screening of peptide aptamers that bind to other unknown emerging infectious disease pathogens that may be pandemic in the future. The peptide aptamers are as small as 30 amino acids and can be easily synthesized and purified as peptides or proteins, or simply used as mRNA drugs. Affiliation